Profil Nitrat dan Fosfat pada Air secara Vertikal di Danau Batur, Bali - Perwira, Ima Yudha; Pertami, Nyoman Dati; Ulinuha, Devi; Fauzan, Farhan Danu (Journal of Marine and Aquatic Sciences; Vol 7 No 1 (2021), 2021)
The aimed of this study was to determine the reproductive biology aspects of longtail tuna, namely the gonad maturity level, gonadal maturity index, fecundity and length of first maturity. Fish samples were obtained from the catches of fishermen in the Bali Strait which landed at PPP Muncar from December 2018 to February 2019. Gonad maturity level of longtail tuna in December 2018 was mostly found in immature conditions (TKG I). TKG III and IV are most commonly found in February. The highest IKG value was found in February 2019 (0.017). This can be interpreted that lontail tuna experienced peak spawning and was actively reproducing in February. The sex ratio of gray tuna is dominated by male. Fecundity at TKG III ranged from 18,800 to 33,200 grains and at TKG IV of 154,000 grains. The length of first maturity of longtail tuna was 495 mmFL (male) and was 487 mmFL (female).